2017
DOI: 10.1590/1983-40632017v4749537
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbits powdery mildew race identity and reaction of melon genotypes1

Abstract: Genetic resistance is one of the most suitable strategies to control cucurbit powdery mildew (CPM) on melon, incited by Podosphaera xanthii or Golovinomyces orontii. However, many races of these pathogens have been reported worldwide in recent years, what may compromise the effectiveness of this method. Thus, annual surveys of CPM races and the screening of germplasm for new sources of genetic resistance provide a vital support to melon breeding programs. This study aimed at identifying a natural population of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
0
5
0
2
Order By: Relevance
“…Previous studies demonstrated that disease resistance screening was important to get tolerant germplasm for breeding new cultivars to control powdery mildew in field and greenhousegrown pumpkins (Luitel et al, 2016;Rabelo et al, 2017). Furthermore, the activation speeds and activity levels of defense enzymes vary in different plant genotypes or plant-pathogen interactions (Yan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that disease resistance screening was important to get tolerant germplasm for breeding new cultivars to control powdery mildew in field and greenhousegrown pumpkins (Luitel et al, 2016;Rabelo et al, 2017). Furthermore, the activation speeds and activity levels of defense enzymes vary in different plant genotypes or plant-pathogen interactions (Yan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…P. xanthii is more frequently found in subtropical and tropical regions as well as in greenhouse crops (Natarajan et al 2016, Ning et al 2014. P. xanthii is emerging as the predominant pathogen in most countries (Bardin et al 1999, Hosoya et al 1999, Hudson et al 2018, McCreight 2006, Ning et al 2014, Pino et al 2002, Zhang et al 2012. Based on the reactions of isolates to melon differential lines, more than 28 physiological races of P. xanthii have been characterized (McCreight 2006).…”
Section: Resistance To Other Diseasesmentioning
confidence: 99%
“…Salah satu solusi efektif yang dapat dilakukan untuk mengontrol penyakit embun tepung adalah melalui pemuliaan tanaman dengan menggunakan kultivar tanaman yang resisten terhadap penyakit ini (Rabelo et al, 2017). Penelitian mengenai analisis ketahanan tanaman melon terhadap infeksi penyakit embun tepung sudah dilaporkan oleh beberapa peneliti (Aristya, Suryanto, Kasiamdari, & Daryono, 2013;C.…”
Section: Pendahuluanunclassified